Faith, family & the feast : recipes to feed your crew from the grill, garden, and iron skillet - Rollins, Kent (Houghton Mifflin Harcourt, 2020)
"The stars of the YouTube channel Kent Rollins Cowboy Cooking, authors of the hit cookbook A Taste of Cowboy, serve up spins on Southern and Western favorites, with a side of spiritual values"--